Moderating Role of Impulsivity Between Depression and Suicidal Ideation Among University Students - Dar, Sabiha; Baloch, Rabail; Usman, Mubara (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: The aim of this research was to examine the moderating effect of impulsivity in the relationship between suicidal ideation and depression in college students. Method: The current study employed a cross-sectional correlational methodology to determine the association between the variables. G power was used to determine the sample size, and the convenient sampling procedure was used to select 200 participants, with age range of 18 to 25 years. The information was gathered from various universities in Lahore, Punjab, Pakistan. Participants' demographic information, the Barratt's Impulsiveness Scale, the Columbia Suicide Severity Rating Scale (C-SSRS), and the Depression, Anxiety, and Stress Scale—21 Items (DASS-21) were utilized to collect data. The data was analyzed using SPSS version 24, and the Person product moments correlation and regression analysis tests were used to validate the results. Results: The results of these investigations are reported, our findings, which show that impulsivity significantly positively attenuated the link between suicidal ideation and depression [β =.403, = 0.637; p <0.05] among university students. Conclusion: The recent study revealed that impulsivity is important in the link between depression and suicidal ideation.